2009
DOI: 10.1002/dc.21009
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic diagnostic pitfall of dermatofibrosarcoma protuberans masquerading as primary parotid tumor: A case report

Abstract: We report the cytology of a rare case of dermatofibrosarcoma protuberans (DFSP) involving the parotid region. Our patient was a 55-year-old female who presented with a swelling in the right parotid region, which was clinically interpreted as a "recurrent parotid tumor." Fine needle aspiration revealed a moderate cellular yield with spindle cell component, seen discretely as well as, embedded loosely within a fibrillary magenta matrix. A few cellular spindle cell fascicles and several discrete, naked, spindly n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Thus it is possible that the ACR captured a greater proportion of DFSP cases in the Alberta population than studies reporting a lower incidence . Third, the diagnosis of DFSP is not always straightforward, particularly if presenting in an uncommon location or biopsied using fine needle aspiration . In one review of the cytologic smears of 12 patients with primary, recurrent, or metastatic DFSP, only six were given the correct diagnosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus it is possible that the ACR captured a greater proportion of DFSP cases in the Alberta population than studies reporting a lower incidence . Third, the diagnosis of DFSP is not always straightforward, particularly if presenting in an uncommon location or biopsied using fine needle aspiration . In one review of the cytologic smears of 12 patients with primary, recurrent, or metastatic DFSP, only six were given the correct diagnosis .…”
Section: Discussionmentioning
confidence: 99%
“…8 Third, the diagnosis of DFSP is not always straightforward, particularly if presenting in an uncommon location or biopsied using fine needle aspiration. 22,23 In one review of the cytologic smears of 12 patients with primary, recurrent, or metastatic DFSP, only six were given the correct diagnosis. 22 The most commonly used cellular marker for pathologic diagnosis of DFSP (CD34) was not widely described in the literature as a marker of this tumor until the early to mid-1990s, increasing the possibility of diagnostic inaccuracy before this time 24 Thus, the large discrepancy between the overall incidence obtained in our study and that obtained others could be due to a multitude of factors.…”
Section: E P I D E M I O L O G Y D F S P a L B E R T A C A N A D Amentioning
confidence: 99%
“…We next conducted a review of the contemporary literature from January 1990 to July 2010 and identified 170 reported cases of malignant mesenchymal cell tumors of the salivary glands, in addition to the 17 cases in our series. Rhabdomyosarcoma was the most common neoplasm, representing 13% of cases, with a median age at diagnosis of 7 years.…”
Section: Resultsmentioning
confidence: 99%
“…These tumors occur mainly over the trunk and proximal extremities and tend to recur after wide local excision. Parotid gland or parotid region is a very rare site with few published case reports [2].…”
Section: Discussionmentioning
confidence: 99%
“…Dermatofibrosarcoma protuberans (DFSP) is a relatively uncommon soft tissue neoplasm of intermediate- to low-grade malignancy. The incidence of sarcomas of the major salivary gland appears to be about one-tenth of benign mesenchymal tumors [2,3]. Metastasis occurs rarely.…”
Section: Introductionmentioning
confidence: 99%